PERAN KELOMPOK INFORMASI MASYARAKAT (KIM) DALAM PEMBERDAYAAN POTENSI LOKAL DI KAMPUNG JAMBU DESA KARANGSONO KECAMATAN KANIGORO KABUPATEN BLITAR - Faidatu Rohmah,; Mutrofin (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2021)
This study aims to describe the role of Community Information Groups (KIM) in forming agricultural business networks in order to improve the community's economy through empowering local potentials in Karangsono Village, Kanigoro District, Blitar Regency. The approach used is to use the theory of diffusion of innovation which has 4 elements of the innovation diffusion process, namely innovation, communication channels, time and social system. However, researchers are more focused on the process of diffusion of innovations in forming a network using communication channels. This study will explain the innovations of KIM members which will be disseminated to the public using qualitative descriptive methods. This research data collection through interviews and field observations. The results of this study are the diffusion of innovation in forming business networks through communication channels that have been created by KIM members. So that the innovation process that has been disseminated can be accepted by the community and can change the community to be more prosperous.